Physicochemical Properties of Red Beetroot and Quince Fruit Extracts Instant Beverage Powder: Effect of Drying Method and Maltodextrin Concentration - Marziyeh Hajiaghaei; Akram Sharifi (Journal of Food Quality)
In this study, production of instant beverage powder by the foam-mat drying method (foam-mat freeze- and hot-air drying) from red beetroot, quince fruit, and cinnamon extracts without and with maltodextrin (MD) (0%, 10%, 20%, and 30%) were investigated. The results showed that an increase in the MD level has led to a decrease in the moisture content of powders. Drying method and MD concentration had a significant effect on rehydration time, color, and total phenolic content (p≤0.05). Foam-mat hot-air-dried powder containing 20% MD had a good flowability. According to the statistical analysis, MD content had a more significant effect on the antioxidant activity of powders than the drying method (p≤0.05). The total phenolic content of foam-mat hot-air-dried powders was higher than that of foam-mat freeze-dried powders. Based on the results, the produced powder containing 20% MD via foam-mat hot-air drying (60°C) was the optimum sample.